Perception of Mg adsorption on the BC2N nanotube as a anode for rechargeable Mg ion batteries. (5th August 2022) - Jassim, Ghufran Sh.; Taban, Taleeb Zedan; Shadhar, Mohanad Hatem; Kadhim, Mustafa M.; Noori, Aiyah S.; Almashhadani, Haider Abdulkareem; Rheima, Ahmed Mahdi; Mohamadi, Ali
Abstract: Owing to their cost-effectiveness and the natural abundance of magnesium, magnesium-ion batteries (MIBs) were introduced as encouraging alternatives to Lithium-ion batteries. Following the successful synthesis of carbon nano-tube, its B and N doped derivatives which were doped with B and N enjoyed the attention of researchers as novel anode materials (AM) for MIBs. Here, we investigated a BC2 N nano-tube (BC2 NNT) as an encouraging AM for MIBs. To have a deeper understanding of the electrochemical properties, cycling stability, specific capacity (SC) and the adsorption behavior of this nano-tube, first-principles density functional theory computations were performed. By performing NMR calculations, we identified two types of non-aromatic hexagonal rings, namely B2 C2 N2 (I) and BC4 N (II). Magnesium was adsorbed onto I with the adsorption energy of −40.38 kcal/mol and on II with the adsorption energy −20.15 kcal/mol. The SCs were as high as 783 mAh/g. The predicted average open-circuit voltage for BC2 NNT was 1.94 V, which was greater than that of other 2D materials. The findings demonstrated the possibility of utilizing the BC2 NNT as an AM for MIBs. The results can provide useful insights into the design of boron-carbon-nitrogen-based AMs for MIBs. Graphical abstract: Image 1 Highlights: DFT was performed for understanding the anodic properties of BC2 NNTs for MIBs. Mg preferably adsorbs on nearly B atom with Ead −40.38 kcal/mol. The Eb have low values (0.07 eV), indicating that the MIBs in the BC2 NNTs.